An Analysis of Air Traffic Growth - Wallace, William M. (The Review of Economics and Statistics, 1963)
The history of air traffic forecasting presents some interesting contrasts in methods and results, as well as some useful insights into the cause and effect of trends. The underlying philosophies of past forecasts, along with their special assumptions, showed great variety. As might have been expected, the numerical results were equally diverse, and many of them proved to be remarkably inaccurate. In the lower forecasts, a share of the market approach was used. It was assumed that air traffic would grow as an integral part of the whole common carrier market: this had been stable for 20 years, and except under the abnormal conditions of World War II, no growth was registered. An inherently stable common carrier was therefore a basic underlying premise and within this static the various modes were simply to exchange their relative places. Air travel, it was predicted, would gradually displace rail travel as the dominant form. The measure of such traffic is commonly the revenue passenger mile. The higher forecasts assumed that air traffic would be independent of the total common carrier curve and that, with certain other assumptions, it would follow or exceed recent trends. Professor Wright's I957 forecast forecasted a jet impact which would accelerate an already steep trend. In another case, lower fares, predicated on the higher productivity, were assumed. Instead, fares were raised. The purpose of this study is to develop a better understanding of what has actually happened and to isolate and analyze the underlying historical patterns. The first pattern examined was the tendency of the growth curve to flatten out in I937, I942, I947-I948, and I958. See Chart I. These pauses could not be explained by economic recession. I937 and 1947-8 were not, in the context of the times, recession periods. The leveling off in I942 was caused by war conditions, rather than depressions. Yet, during actual recession years (1938, I949, I953-54), air traffic continued its dynamic growth. I958 is one period in which there was both a recession and a pause in air traffic growth . . . hardly a valid basis for establishing a cause and effect relationship.